Medical polyurethane with controllable degradation rate and preparation method thereof
Through the method of copolymerizing glycolic acid and neopentyl glycol and synthesizing with isocyanate and polyethylene glycol, the problem of limited application of PGA in the biomedical field is solved, the controllable degradation rate and improved performance are achieved, and the adaptability is provided. Medical polyurethane materials for application scenarios.
Patent Information
- Application Number
- CN202411489151.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
AI Technical Summary
The application of polyglycolic acid (PGA) in the field of biomedical science is limited by its high crystallinity, high melting point, difficulty in processing and forming, poor water absorption and uncontrollable degradation rate.
Polyglycolic acid polyols are prepared by copolymerizing glycolic acid and neopentyl glycol, and degradable medical polyurethanes are synthesized with isocyanate and polyethylene glycol under the action of catalysts, and the proportion of polyethylene glycol is adjusted to control the degradation rate and mechanical properties.
The medical polyurethane with controllable degradation rate was successfully synthesized, which improved the brittleness and hydrophilic properties of PGA, expanded its application potential in the field of biomedical science, and provided environmentally friendly products.
Smart Images

Figure HSA0000299778180000011 
Figure HSA0000299778180000021 
Figure HSA0000299778180000022
Abstract
Description
Technical Field
[0001] The invention relates to the intersecting field of medical degradable materials and green chemistry, and in particular to a preparation method of medical glycolic acid-based polyurethane. Background Art
[0002] Polyurethane (PU) is a type of polymer with repeated urethane groups. Due to its unique microphase separation structure similar to biological membranes, it has good biocompatibility and is widely used in the field of biomedical engineering, such as hemodialysis catheters, artificial heart valves, artificial blood vessels and medical dressings. The reactive functional groups of its main reactant diisocyanate can react with various groups with active hydrogen (such as amino groups, etc.), so it is possible to flexibly design molecules and synthesize copolymers with different performance requirements. Degradable polyurethane is synthesized with aliphatic diisocyanate as hard segment and polyol as soft segment, and can be decomposed into small molecules that can be absorbed and metabolized by organisms; degradable medical polyurethane materials have attracted much attention in recent years due to their environmentally friendly characteristics and the industry's demand for the development of new medical materials.
[0003] Polyglycolic acid (PGA) has the advantages of high strength, good biocompatibility, high water and oxygen barrier rate, and biodegradability. However, it has high rigidity, poor toughness, high glass surface temperature, poor processability, poor hydrophilicity, and is hard and brittle at room temperature, which makes it unable to meet the requirements in the application of biomedicine, which greatly limits its application prospects.
[0004] Polyethylene glycol (PEG) is the polymer with the lowest absorption level by proteins and cells among all known polymers. At room temperature, polyethylene glycol is easily soluble in water, ethanol and most common solvents, and is non-toxic, harmless and non-irritating to the human body. It has good biocompatibility, lubricity and moisturizing properties. It can be widely used in medical device materials such as adhesion, hemostasis, leakage prevention and adhesion prevention in various surgical operations on the human body. At the same time, polyethylene glycol materials can also be used as raw materials for medical devices implanted in the human body, replacing the currently widely used plant-based, animal-based and human-based materials, so it has extremely wide medical uses.
[0005] The use of polyglycolic acid diol (PGA diol) to prepare polyurethane products can increase the hydrophilicity of polyglycolic acid, thereby adjusting the degradation rate, and effectively improve the brittleness of PGA and other problems, expand the application performance of PGA, and give polyurethane better biodegradability, thereby providing an environmentally friendly product; related research has not been reported. The technical problem to be solved by this technical solution is the problem of limited application of PGA in the biomedical field. Summary of the invention
[0006] In view of the problems of high crystallinity, high melting point, difficult processing and molding, poor water absorption and unchangeable degradation rate of PGA, a medical polyurethane with controllable degradation rate and its preparation method were invented. Polyglycolic acid polyol was prepared by copolymerization with neopentyl glycol using glycolic acid as raw material; the obtained polyol was combined with isocyanate and polyethylene glycol in the presence of a catalyst to synthesize degradable medical polyurethane.
[0007] The present invention adopts the following technical solutions:
[0008] Step S1, glycolic acid, neopentyl glycol, and stannous octoate are added into a three-mouth glass reactor in proportion, nitrogen is first introduced to replace the air in the reactor, and then the system is heated to 120-180° C. for reaction for 8-20 hours to obtain polyglycolic acid diol.
[0009] Step S2, rinsing the PGA diol with deionized water, and placing the rinsed PGA diol in an oven for drying;
[0010] Step S3, weighing PGA diol and polyethylene glycol, adding PGA diol and polyethylene glycol into an open reactor, assembling a reaction device, weighing dicyclohexylmethane diisocyanate (HMDI) for standby use, and setting the oil bath temperature of the oil bath pot to 80° C.;
[0011] Step S4, when the oil bath is heated up, the stirrer is turned on to stir the PGA diol and polyethylene glycol in the open reactor;
[0012] Step S5, after the oil bath temperature reaches 80°C, stannous octoate catalyst is added dropwise, and 1% of the weighed amount of HMDI is added every 20 seconds. At this time, it is found that the viscosity of the system gradually increases;
[0013] Step S6, after adding one tenth of the weighed amount of HMDI, the oil bath temperature is set to 90° C., and one percent of the weighed amount of HMDI is added every 30 seconds;
[0014] Step S7, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 100° C., and one percent of the weighed amount of HMDI is added every 40 seconds;
[0015] Step S8, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 110°C, and one percent of the weighed amount of HMDI is added every 50 seconds until the remaining HMDI is added, and the oil bath temperature is set to 120°C;
[0016] Step S9, ensuring that the reaction temperature in the system is stable, stopping stirring after ten minutes, and pouring out the product;
[0017] Step S10: The product obtained in step S8 is naturally cooled to room temperature to obtain the finished product.
[0018] As a preferred technical solution of the present invention, in step S2, the PGA diol is rinsed with deionized water, and the rinsed PGA diol is placed in an oven for drying.
[0019] As a preferred technical solution of the present invention, in step S3, the proportions of the components are, by weight percentage, 38.6%-100% PGA diol, 0%-38.6% polyethylene glycol, and 22.8%-31.6% HMDI, and the diol mixture in the open reactor is melted into a transparent liquid.
[0020] As a preferred technical solution of the present invention, in step S4, the stirring speed of the stirrer is 140 rpm, and the diol mixture in the open reactor melts into a transparent liquid.
[0021] As a preferred technical solution of the present invention, in step S5, the amount of the organotin catalyst is 1‰ to 3‰ of the total amount of PGA diol and polyethylene glycol, and the organotin catalyst includes stannous octoate, stannous oleate, and dibutyltin dilaurate.
[0022] Beneficial effects of the present invention: The present invention successfully synthesizes a medical polyurethane with controllable degradation rate based on PGA diol and polyethylene glycol through HMDI chain extension. The hydrophilicity of polyethylene glycol is better than that of PGA diol. Therefore, by adjusting the proportion of polyethylene glycol, the water absorption of the synthesized medical polyurethane can be adjusted to regulate the degradation rate of the medical polyurethane. The molecular weight of polyethylene glycol is relatively higher than that of PGA diol. Therefore, by adjusting the proportion of polyethylene glycol, the mechanical properties of the synthesized polyurethane can be adjusted. By adjusting the proportion of PGA diol and polyethylene glycol, polyurethane materials of strong and tough, hard and brittle, soft and tough, and soft and weak types can be synthesized to meet the needs of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a biodegradation rate curve diagram of TPU samples with different PGA diol contents of the present invention;
[0024] Figure 2 It is the stress-strain curve diagram of the TPU sample of the present invention;
[0025] Figure 3 This is the appearance of TPU samples with different PGA diol contents of the present invention. DETAILED DESCRIPTION
[0026] In order to make the technical solution and advantages of the present invention more clear, the technical solution of the present invention will be described clearly and completely in combination with the embodiments of the present invention below, but it should not be understood as limiting the scope of implementation of the present invention.
[0027] Example 1
[0028] like Figures 1 to 3 As shown, the present invention discloses a medical polyurethane with controllable degradation rate and a preparation method thereof, and the technical scheme adopted includes the following steps.
[0029] Step S1, glycolic acid, neopentyl glycol, and stannous octoate are added into a three-mouth glass reactor in proportion, nitrogen is first introduced to replace the air in the reactor, and then the system is heated to 120-180° C. for reaction for 8-20 hours to obtain polyglycolic acid diol.
[0030] Step S2, rinsing the PGA diol with deionized water, and placing the rinsed PGA diol in an oven for drying;
[0031] Step S3, weighing PGA diol and polyethylene glycol, adding PGA diol and polyethylene glycol into an open reactor, assembling a reaction device, weighing HMDI for standby use, and setting the oil bath temperature of the oil bath pot to 80° C.;
[0032] Step S4, when the oil bath is heated up, the stirrer is turned on to stir the PGA diol and polyethylene glycol in the open reactor;
[0033] Step S5, after the oil bath temperature reaches 90°C, stannous octoate catalyst is added dropwise, and 1% of the weighed amount of HMDI is added every 20 seconds. At this time, it is found that the viscosity of the system gradually increases;
[0034] Step S6, after adding one tenth of the weighed amount of HMDI, the oil bath temperature is set to 100° C., and one percent of the weighed amount of HMDI is added every 30 seconds;
[0035] Step S7, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 110° C., and one percent of the weighed amount of HMDI is added every 40 seconds;
[0036] Step S8, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 120°C, and one percent of the weighed amount of HMDI is added every 50 seconds until the remaining HMDI is added, and the oil bath temperature is set to 120°C;
[0037] Step S9, ensuring that the reaction temperature in the system is stable, stopping stirring after ten minutes, and pouring out the product;
[0038] Step S10: The product obtained in step S9 is naturally cooled to room temperature to obtain the finished product.
[0039] As a preferred technical solution of the present invention, in step S2, the PGA diol is rinsed with deionized water, and the rinsed PGA diol is placed in an oven for drying;
[0040] As a preferred technical solution of the present invention, in step S2, the proportion of each component by weight is 38.6% PGA diol, 38.6% polyethylene glycol, and 22.8% HMDI, specifically 20g PGA diol, 20g polyethylene glycol, and 11.84g HMDI. The diol mixture in the open reactor melts into a transparent liquid.
[0041] As a preferred technical solution of the present invention, in step S3, the stirring speed of the stirrer is 140 rpm, and the diol mixture in the open reactor melts into a transparent liquid.
[0042] As a preferred technical solution of the present invention, in step S4, the amount of stannous octoate catalyst used is 0.08 g.
[0043] The finished product obtained based on Example 1 can be referred to as Sample TPU-1
[0044] Example 2
[0045] The difference between this embodiment and embodiment 1 is that, by weight percentage, the proportions of the components are: PGA diol 45.1%, polyethylene glycol 30.1%, HMDI 24.8%, specifically, PGA diol 12g, polyethylene glycol 8g, HMDI 6.58g.
[0046] The finished product obtained based on Example 2 can be called sample TPU-2.
[0047] Example 3
[0048] The difference between this embodiment and embodiment 1 is that, by weight percentage, the proportions of the components are: PGA diol 51.3%, polyethylene glycol 22.0%, HMDI 26.5%, specifically, PGA diol 14g, polyethylene glycol 6g, HMDI 7.24g.
[0049] The finished product obtained based on Example 3 can be called sample TPU-3.
[0050] Example 4
[0051] The difference between this embodiment and embodiment 1 is that, by weight percentage, the proportions of the components are: PGA diol 57.3%, PPC diol 14.3%, HMDI 28.3%, specifically, PGA diol 16g, polyethylene glycol 4g, HMDI 7.90g.
[0052] The finished product obtained based on Example 4 can be called sample TPU-4.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 1 is that, by weight percentage, the proportions of the components are: PGA diol 63.0%, polyethylene glycol 7.0%, HMDI 29.9%, specifically, PGA diol 18g, polyethylene glycol 2g, HMDI 8.56g.
[0055] The finished product obtained based on Example 5 can be called sample TPU-5.
[0056] Example 6
[0057] The difference between this embodiment and embodiment 1 is that, by weight percentage, the proportions of the components are: PGA diol 68.43%, polyethylene glycol 0, HMDI 31.57%, specifically PGA diol 8.80g, polyethylene glycol 0g, HMDI 9.23g.
[0058] The finished product obtained based on Example 6 can be called sample TPU-6. Testing and Characterization
[0059] Biodegradation performance test:
[0060] The TPU samples were tested by immersing the samples in a PBS solution (pH = 7.4, 37°C) for 28 days and monitoring weight loss and morphological changes. The samples were cut into a certain size (20 mm in diameter and 1 mm in thickness) and pre-wetted with PBS to ensure penetration through the sample. Each sample was immersed in a 15 ml centrifuge tube containing 10 ml of PBS solution, and the centrifuge tube was kept in an incubator at 37°C. After incubation for different durations (7, 14, 21 and 28 days), the samples were removed from the solution, rinsed with distilled water, and dried in a vacuum oven at 40°C for 12 hours. The weight loss was calculated by the following equation: Weight loss = (W 0 -W 1 ) / W 0 × 100%, where W 0 and W t is the original weight and the weight of the sample after soaking in PBS for the tth day, and we get Figure 1 .
[0061] Tensile properties test:
[0062] The tensile properties were tested using a microcomputer-controlled electronic universal testing machine from Meters Industrial Systems (China) Co., Ltd. After the TPU pellets were passed through a mold on a flat vulcanizer to obtain dumbbell-shaped specimens, the tensile yield strength and elongation at break of the sample were measured using the tensile-displacement mode at a tensile rate of 50 mm / min. The tensile modulus of the sample was measured using the tensile-small extensometer mode at a tensile rate of 1 mm / min. Five valid values were taken and the average value was used as the final result. Figure 2 .
[0063] Morphological characteristics of TPU samples:
[0064] like Figure 3 As shown, the appearance of the TPU samples obtained in different embodiments is described as follows:
[0065] TPU-1 products have a smooth and glossy surface, are transparent, dark brown in color, have a low hardness, but have an extremely high elongation at break.
[0066] TPU-2 products have a smooth and glossy surface, are transparent, and are dark brown in color. They have increased hardness but reduced toughness.
[0067] The surface of TPU-3 product is smooth and shiny, transparent, dark brown, with high hardness and good toughness.
[0068] TPU-4 product has a smooth, transparent, light yellow surface, high hardness and good toughness.
[0069] The surface of TPU-5 product is smooth, transparent, light yellow, with increased strength but reduced toughness.
[0070] The surface of TPU-6 product is smooth, transparent, light yellow, strong but poor in toughness.
[0071] Components not described in detail herein are prior art.
[0072] Although the specific embodiments of the present invention are described in detail above, the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the purpose of the present invention, and modifications or deformations without creative labor are still within the protection scope of the present invention.
Claims
1. A medical polyurethane with controllable degradation rate and a preparation method thereof, characterized in that: The following steps are included Step S1, glycolic acid, neopentyl glycol, and stannous octoate are added into a three-mouth glass reactor in proportion, nitrogen is first introduced to replace the air in the reactor, and then the system is heated to 120-180° C. for reaction for 8-20 hours to obtain polyglycolic acid diol. Step S2, rinsing the PGA diol with deionized water, and placing the rinsed PGA diol in an oven for drying; Step S3, weighing PGA diol and polyethylene glycol, adding PGA diol and polyethylene glycol into an open reactor, assembling a reaction device, weighing dicyclohexylmethane diisocyanate (HMDI) for standby use, and setting the oil bath temperature of the oil bath pot to 80° C.; Step S4, when the oil bath is heated up, the stirrer is turned on to stir the PGA diol and polyethylene glycol in the open reactor; Step S5, after the oil bath temperature reaches 80°C, an organotin catalyst is added dropwise, and 1% of the weighed amount of HMDI is added every 20 seconds. At this time, it is found that the viscosity of the system gradually increases; Step S6, after adding one tenth of the weighed amount of HMDI, the oil bath temperature is set to 90° C., and one percent of the weighed amount of HMDI is added every 30 seconds; Step S7, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 100° C., and one percent of the weighed amount of HMDI is added every 40 seconds; Step S8, after adding one tenth of the weighed amount of HMDI again, the oil bath temperature is set to 110°C, and one percent of the weighed amount of HMDI is added every 50 seconds until the remaining HMDI is added, and the oil bath temperature is set to 120°C; Step S9, ensuring that the reaction temperature in the system is stable, stopping stirring after ten minutes, and pouring out the product; Step S10: The product obtained in step S9 is naturally cooled to room temperature to obtain the finished product.
2. The method for preparing a medical polyurethane with controllable degradation rate according to claim 1, characterized in that: In the step S2, the PGA diol is rinsed with deionized water, and the rinsed PGA diol is placed in an oven for drying.
3. The method for preparing a medical polyurethane with controllable degradation rate according to claim 1, characterized in that: In the step S3, the proportions of the components are, by weight percentage, 38.6%-100% of PGA diol, 0%-38.6% of polyethylene glycol, and 22.8%-31.6% of HMDI. The diol mixture in the open reactor melts into a transparent liquid.
4. The method for preparing a medical polyurethane with controllable degradation rate according to claim 1, characterized in that: In step S4, the stirring speed of the stirrer is 140 rpm, and the diol mixture in the open reactor melts into a transparent liquid.
5. The method for preparing a medical polyurethane with controllable degradation rate according to claim 1, characterized in that: In step S5, the amount of the organotin catalyst is 1‰ to 3‰ of the total amount of PGA diol and polyethylene glycol, and the organotin catalyst includes stannous octoate, stannous oleate, and dibutyltin dilaurate.
